Integration of ultraviolet sensor and X-ray detector for navigation satellite orbit estimation - Li Qiao; Jianye Liu; Guanglou Zheng; Zhi Xiong (2008 IEEE/ION Position, Location and Navigation Symposium, 2008)
In recent years, X-ray navigation (XNAV) has become of great interest for spacecraft autonomous navigation. The XNAV system can be used as an augmentation to the current navigation capability or as a backup to the Global Position System (GPS) and the deep space network (DSN). In this paper, the XNAV system is used to augment the ultraviolet (UV) sensor based satellite navigation system. In order to simplify the structure of the XNAV system, only one X-ray detector is used. The federated filtering technique is used to process the data from the X-ray detector and the UV sensor. It is analyzed that the XNAV system using one X-ray detector is not completely observable, but the satellite integrated navigation system using these two sensors has a good navigation performance. It is demonstrated on the GPS satellite orbit and the geosynchronous satellite orbit that, the navigation performance of the satellite integrated navigation system is improved a lot with respect to that of the UV sensor-based satellite navigation system.